2019
DOI: 10.1186/s12871-019-0838-z
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled comparison of non-channeled king vision, McGrath MAC video laryngoscope and Macintosh direct laryngoscope for nasotracheal intubation in patients with predicted difficult intubations

Abstract: Background King Vision and McGrath MAC video laryngoscopes (VLs) are increasingly used. The purpose of this study was to evaluate the performance of nasotracheal intubation in patients with predicted difficult intubations using non-channeled King Vision VL, McGrath MAC VL or Macintosh laryngoscope by experienced intubators. Methods Ninety nine ASA I or II adult patients, scheduled for oral maxillofacial surgeries with El-Ganzouri risk index 1–7 were enrolled. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…The operator criteria were defined in all studies except in one [ 32 ]. The types of video laryngoscopes used included Glidescope (three studies) [ 26 , 33 , 34 ], C-MAC D-blade (one study) [ 25 ], McGrath (four studies) [ 27 29 , 31 ], True View EVO2 (one study) [ 30 ], and Pentax Airway scope (two studies) [ 32 , 33 ]. ( Table 1 )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The operator criteria were defined in all studies except in one [ 32 ]. The types of video laryngoscopes used included Glidescope (three studies) [ 26 , 33 , 34 ], C-MAC D-blade (one study) [ 25 ], McGrath (four studies) [ 27 29 , 31 ], True View EVO2 (one study) [ 30 ], and Pentax Airway scope (two studies) [ 32 , 33 ]. ( Table 1 )…”
Section: Resultsmentioning
confidence: 99%
“…The definition of time to intubation varied from the mouth opening until the detection of ETCO 2 [ 25 , 27 , 30 ], end of mask ventilation until detection of ETCO 2 [ 26 ], intranasal placement until detection of ETCO 2 [ 28 ], insertion through nostril until detection of ETCO 2 [ 29 ], passing through the nasal cavity until chest rise [ 31 ], placement of the endotracheal tube [ 32 , 33 ], or as not clear [ 34 ]. Pooled analysis showed a significantly shorter time to intubation favoring VL (MD: −9.04, 95% CI [ –12.71, –5.36], n = 597, P < 0.001, I 2 = 59%) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Haozhen Zhu and colleagues have shown that both non-channeled King Vision and McGrath MAC Video laryngoscopes took significant lesser time for nasotracheal intubation in patients with predicted difficult intubations compared with Macintosh laryngoscope 17 . Use of Macintosh laryngoscope has been conventionally accepted as the first choice for tracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Various manufacturers have specialized in the development of videolaryngoscopes, including the King Vision (Ambu, Copenhagen, Denmark), McGrath MAC (Medtronic, Dublin, Ireland), and the C‐MAC videolaryngoscope (Karl Storz, Tuttlingen, Germany) with the hyper‐angulated D‐blade, which was designed for intubation in patients with difficult anatomical airway conditions. They offer a simpler, faster, and optimal visibility of the vocal cords compared to the conventional Macintosh laryngoscope 21,22 . The aim of the following user study is to examine whether surgical manipulation of the larynx is possible with a modified videolaryngoscope prototype in a porcine ex vivo laryngeal model.…”
Section: Introductionmentioning
confidence: 99%